2021
DOI: 10.3390/metabo11020092
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids and Some Other Pigments from Fungi and Yeasts

Abstract: Carotenoids are an essential group of compounds that may be obtained by microbiological synthesis. They are instrumental in various areas of industry, medicine, agriculture, and ecology. The increase of carotenoids’ demand at the global market is now essential. At the moment, the production of natural carotenoids is more expensive than obtaining their synthetic forms, but several new approaches/directions on how to decrease this difference were developed during the last decades. This review briefly describes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 167 publications
0
27
0
1
Order By: Relevance
“…O aumento da demanda de carotenóides no mercado global tem sido cada vez mais consistente. No momento, a produção de carotenoides naturais é mais cara do que a obtenção de suas formas sintéticas, contudo, várias novas abordagens tem sido relatadas usando fontes naturais (RAPOPORT et al, 2021), uma vez que os resíduos agroindustriais são um recurso natural inexplorado de compostos bioativos, incluindo carotenóides (NAGARAJAN et al, 2020). Dentro desse contexto, a partir da busca científica, foram selecionados 67 trabalhos publicados entre os anos de 2005 à 2021.…”
Section: Resultsunclassified
“…O aumento da demanda de carotenóides no mercado global tem sido cada vez mais consistente. No momento, a produção de carotenoides naturais é mais cara do que a obtenção de suas formas sintéticas, contudo, várias novas abordagens tem sido relatadas usando fontes naturais (RAPOPORT et al, 2021), uma vez que os resíduos agroindustriais são um recurso natural inexplorado de compostos bioativos, incluindo carotenóides (NAGARAJAN et al, 2020). Dentro desse contexto, a partir da busca científica, foram selecionados 67 trabalhos publicados entre os anos de 2005 à 2021.…”
Section: Resultsunclassified
“…Pichia, Rhodotorula, Xanthophyllomyces, Rhodosporidium, Sporobolomyces , and Sporidiobolus are also potent producers of various carotenoids and other pigments. The most commonly produced carotenoids by yeast include β-carotene, torulene, astaxanthin, and canthaxanthin ( Mata-Gómez et al, 2014 ; Rapoport et al, 2021 ). For the optically active astaxanthin, the 3R, 3′R isomeric form is produced by Xanthophyllomyces dendrorhous .…”
Section: Major Classes Of Pigments and Microbial Sourcesmentioning
confidence: 99%
“…For the optically active astaxanthin, the 3R, 3′R isomeric form is produced by Xanthophyllomyces dendrorhous . The torularhodin produced by Sporobolomyces or Rhodotorula genera has robust antimicrobial properties which makes it suitable for many pharmaceutical applications ( Rapoport et al, 2021 ).…”
Section: Major Classes Of Pigments and Microbial Sourcesmentioning
confidence: 99%
“…Carotenoids enhance the nutritional value of a myriad of natural sources, such as fruit and vegetables, eggs, fish, algae, fungi, and yeasts [157,158]. In the human diet, approximately 50 carotenoids can be found [152].…”
Section: Biotechnological Potential and Applicationsmentioning
confidence: 99%
“…Recent reviews regarding carotenoids (from 2016 onwards) can be found, that deal with their potential health benefits [147,151,[162][163][164], bio-accessibility [148,164], metabolism and biosynthesis [149,165], dietary sources [158], production [157,[166][167][168], extraction and analysis [158], and biotechnological potential [167]; again, most of these examples focus on either microalgae or fungi or, at least, they are not solely focused on macroalgae. By searching the word "carotenoid", Patentscope holds 4701 registered patents, using the search field "front page" [16].…”
Section: Biotechnological Potential and Applicationsmentioning
confidence: 99%